Rural community libraries in Africa : challenges and impacts - Dent, Valeda Frances; Goodman, Geoff; Kevane, Michael; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book investigates the relationship between local libraries and community development, from the historical roots of rural libraries to their influence on the literacy, economy, and culture of the surrounding region"--Provided by publisher.
Rural library services in African countries: history, development, and characteristics -- The rural community library in Africa as a context for literacy and reading -- An overview of prior research on select community libraries -- Books for African readers: borrowing patterns at Kitengesa Community Library, Masaka, Uganda / Kate Parry -- Exploring secondary school student factors and academic outcomes at the Kitengesa Community Library -- The intergenerational impact of a rural community library on young children's learning readiness in a Ugandan village -- Beyond reading: impacts on local economic development -- How much does it cost to get a book read?: case study from Burkina Faso -- Cost-effectiveness of a summer reading program in community libraries in Burkina Faso -- Impacts of summer reading camp programs in community libraries in Ghana -- Cost-effectiveness of solar-powered LED reading lamps in Burkina Faso -- Mounting a quantitative or qualitative research study of the rural African village library: lessons learned -- Global initiatives: building and advancing rural community libraries -- Conclusion / Valeda F. Dent, Geoff Goodman, Michael Kevane.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 11/27/2013).
Keywords: Rural libraries -- Africa; Libraries and community -- Africa; Books and reading -- Africa; Literacy programs -- Africa; Borrowing patterns; Community enrichment; Cost analysis; Economic development; Educational impact; Growing libraries; Rural library services; Electronic books